Prevalence and morphological assessment of bifid mandibular canal using cone beam computed tomography among a group of yemeni adults - Nabil Qaid; Abdulwahab Aldilami; Khaled AL-Jawfi; Anas Shamala (Wolters Kluwer Medknow Publications, 2021)
Objectives: The study aimed to assess the prevalence and morphology of bifid mandibular canal (BMC) using cone beam computed tomography (CBCT) among a group of Yemeni adults. Materials and Methods: The presence and type of BMC were evaluated among 400 CBCT images. Prevalence rate of BMC was also determined according to gender. Further, the diameter and length of BMCs were measured using Ez3D plus software. Chi-square analysis and the analysis of variance (one-way ANOVA) were used. Results: The study concluded that BMCs were found in 60 (15%) of total cases. There was no significant correlation between gender and BMC prevalence. Forward BMC was the most common type (48.3%), followed by retromolar BMC (35.0%) then dental BMC (16.7%); while not even one case of buccolingual BMC was observed. There was a significant difference in the mean diameter of BMC (P value = 0.016). There was a significant difference in the mean length of BMC (P = 0.001). Conclusion: The prevalence of BMCs in Yemeni adults is relatively high, and forward BMC was the most common type. Detecting BMCs by using CBCT imaging is highly recommended prior to any mandibular surgery.